#TITLE_ALTERNATIVE# - Made Arnawa (NIM 20197501), I
ABSTRACT: Let H be a Hilbert space. A frame in H is a set of vectors in H, not necessarily orthonormal, which can be used to write a straightfoward and completely explicit expansion for every vector in H. In this thesis, basic theory of frames is discussed. Further, a special kind of frames for L (R), called Gabor frames, including its necessary and sufficient conditions will be studied.